Spatiotemporal Variation of Drought in Shandong Province Analyzed Using the Standardized Precipitation-evapotranspiration Index - REN Jiancheng; WANG Feng; LU Xiaoning (Guan'gai paishui xuebao, 2021)
【Objective】 Global warming has been resulting in more extreme weather events such as drought and flooding, and understanding their severity and frequency is important for improving management to mitigate their detrimental impact. Taking Shandong province as an example, this paper analyzes the spatiotemporal variation of droughts over the past 40 years in the province. 【Method】 Monthly temperature and precipitation measured from 1981 to 2020 at 25 meteorological stations across the province were collected. Standardized precipitation evapotranspiration index (SPEI) at each station was calculated at both seasonal and annual scales, from which we calculated the spatiotemporal variation of droughts in the province using linear regression, Tyson polygon, spatial interpolation and wavelet analysis. 【Result】 ①Summer precipitation had been in decline while annual precipitation had been in increase, though neither was at significant level. Meanwhile, seasonal and annual temperature had both been in increase at significant level. ②At seasonal and annual scales, dry and wet weather occurred alternately, and the summer alternation annual alternation remained almost unchanged over the 40 years. ③The areas suffering spring and summer droughts had been in increase while areas hit by autumn and winter throughs had been in decline, though neither was at significant level. ④The frequency of spring drought increased gradually from the southwest-southeast to the north, though spatial difference in summer and annual droughts across the province was small. The frequency of autumn drought increased gradually from the north to the south, while the frequency of winter drought increased gradually from the southwest to the northwest-southeast. ⑤Seasonally, the identified drought periods are 10, 29, 4 and 17 a in spring, 20, 4, 7 and 10 a in summer, 14, 6, 25, 8 and 3 a in autumn, 5, 24, 16 and 10 a in winter. Annually, the periods were 23, 14, 4, 10 and 7 a. 【Conclusion】 Temperature rise in Shandong province was significant, but the change in precipitation was not significant, with dry and wet occurring alternately.